The Measurement of Positive Valence Forms of Empathy and Their Relation to Anhedonia and Other Depressive Symptomatology - Light, Sharee N.; Moran, Zachary D.; Zahn-Waxler, Carolyn; Davidson, Richard J. (Frontiers in Psychology, 2019)
Construct validity of a brief self-report measure of “positive-valence empathy” (the tendency to exude positive emotion as a means to stimulate positive affect in others, and/or to vicariously share in another's positive emotion; Light, Coan, Zahn-Waxler, Frye, Goldsmith & Davidson, 2009) was attained utilizing a sample of 282 healthy adults. Positive-valence empathy may have unique predictive ability for differentiating depression versus depression with anhedonia. Confirmatory factor analyses revealed a two-factor structure for the final 15-item Light-Moran Positive Empathy Scale (PES), with an 8-item "Empathic Happiness" subscale (e.g. "I find that other people's happiness easily rubs off on me") and a 7-item "Empathic Cheerfulness" subscale (e.g. "I enjoy making others feel good"). "Empathic Happiness" was a significantly better predictor of overall depressive symptomatology (Beck, Steer & Brown, 1996) than anhedonia (Snaith, Hamilton, Morley, Humyan, Hargreaves & Trigwell, 1995). The Light-Moran PES-15 may have real-world impact and predictive utility for well-being.